Kedudukan dan Fungsi Lembaga Negara dalam Sistem Pemerintahan Indonesia - Bemby Navita; Rosita Adelia Putri; Jacinda Az Zahra; Aurellia Mirabel Fredlyna; Stephanus Louis Scaeva Tapiheru; Kuswan Hadji (Pusat Riset dan Inovasi Nasional, 2025)
This article discusses the position and functions of state institutions in Indonesia's governmental system based on the 1945 Constitution (UUD 1945). The UUD 1945, as Indonesia's highest written constitution, establishes state institutions within three main branches of government: executive, legislative, and judicial. The article outlines how each branch fulfills its role according to the principle of trias politica, aimed at maintaining a balance of power through a system of checks and balances. The main focus is to analyze the position of these institutions within the constitutional framework and how they work synergistically to support Indonesia's political, legal, and social stability. Furthermore, the article explores the challenges faced by state institutions, such as overlapping authorities, and offers recommendations for addressing these issues to strengthen good governance and democracy. A deeper understanding of the role and functions of state institutions is expected to help Indonesia achieve a just and prosperous government.